Detection of Salmonella sp. and Escherichia coli on Chicken Meat at Tamiang Layang Market: Detection of Salmonella sp. and Escherichia coli on Chicken Meat at Tamiang Layang Market - AKHMAD RIZALDI; ENGKI ZELPINA (Microbiology Indonesia, 2020)
Salmonella sp. and Escherichia coli (E. coli) are the two most important pathogens because they are indicators of food safety and sanitation indicators because they can potentially pose a high risk of foodborne disease. This study aims to look at the prevalence of Salmonella sp. and E. coli in the Tamiang Layang Market as supervision of food safety. A total of 6 chicken breast samples were taken at all chicken traders in the Tamiang Layang market. Testing the presence of Salmonella sp. and E. coli using MC-Media Pad. The existence of Salmonella sp. and E. coli in chicken meat at the Tamiang Layang market were 66.6% and 83.3%. The need to improve the hygiene and sanitation of chicken traders.